KUALITAS PELAYANAN JASA BONGKAR MUAT BARANG PADA PT. (PERSERO) PELABUHAN INDONESIA II CABANG PONTIANAK - Fitri Afrianto E.21107013 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The focus of this research is the analysis of the capability of PT Pelindo II of Pontianak Branch as a provider of services of loading and unloading goods accurately include the assurance of the accuracy of the service or the provision of services. In carrying out the activities of loading and unloading of goods in accordance with the standards of the time and the procedures that apply throughout the PT Pelindo II in Indonesia is a 2-day working period. The ability of officers in mengoperasionalisasikan modern technology to provide the service of unloading stuff online is good. Generally the responsibility of the attendant services of loading and unloading of goods on the work of the already quite good, despite the constraints caused by the system/network crashes/error. The officer's attitude in the face of customer complaints against the service system of loading and unloading of goods through the online booking system stack error or crashes yet satisfying user service loading and unloading of goods. In order to improve services to users of the service (cruise), PT Pelindo II of Pontianak Branch should make efforts include: perform network maintenance, renew products and services always provide briefing-briefing or instructions to the loading and unloading of goods services. Keywords: Reliability, tangibles, empathy,  responsiveness.